The Role of Employee Services and Facilities Against The Interests of Visitors to The Grand Kolopaking Hotel Kebumen, Central Java, Indonesia - Barreto, Ananias; Langlang Buana, Ken Ramadhan; Rachmadian, Aprilia (Jurnal Pariwisata Tourista, 2023)
This study aims to determine the partial and simultaneous effect of service quality and facilities on visitors' interest in using lodging services at the Grand Kolopaking Hotel, Kebumen. The sample specified in this study is that consumers use lodging services at the Grand Kolopaking Kebumen Hotel, namely as many as 100 respondents. The data collection method in this study was by distributing questionnaires or questionnaires to samples that match the research criteria. This research is a quantitative descriptive study using the SPSS V.21 data processing program. In this study, based on the t test conducted, it shows that the service quality variable has no effect on visitor interest, while facilities have a positive and significant effect on visitor interest. Through the F test it is known that simultaneously the dependent variable has an effect on the independent variables and facility variables. While the rest is explained by other variables not examined in this study, such as promotions, perceived quality. From the research results, it was also found that the facility variable was the variable that had the dominant influence on visiting intentions.